An Empirical Study to Compute the Efficiency of Indian Banks During the Pre and Post Periods of Recession with the Help of Data Envelopment Analysis - Banerjee, Arindam (Indian Journal of Finance, 2018)
The present study was undertaken to measure the efficiency of Indian commercial banks during the pre and post periods of the recent global recession. Data envelopment analysis (DEA) as an operation research technique was utilized to measure the efficiency of commercial banks in the Indian scenario. Input oriented variable return to scale approach was used in this study. Linear program was formulated to compute the efficiency and super efficiency scores of different commercial banks. The banks were ranked according to the scores obtained by them during the period of the study. The pre recession period was taken from 2001-2002 to 2006-2007 and the post recession period was considered from 2007-2008 to 2012-2013. Further endeavor was made in this study to understand if there was a significant difference between the ranks obtained by commercial banks during pre and post periods of recession by utilizing Spearman's rank correlation. It was concluded from the study that recession had a little impact on the performance of Indian commercial banks in general, though private sector banks were able to fare better than their public sector counterparts during the post recession period as compared to the pre recession period.